On Public Awareness of HIV Risk Factors - Yuldasheva F.U; Sherkuzieva G. F.; Mirsagatova M.R.; Niyazova O.A (Genius Journals, 2024)
AIDS is a chronic infectious disease affecting the human immune system, blood-borne and sexually transmitted. AIDS began to spread in South and South-East Asia in the early 1990s. More than 1 million people have already been infected with HIV in 2004, and more than 8 million people in South and South-East Asia are now infected with the human immunodeficiency virus (HIV), 30 per cent of the world’s population. Every day, some 15,000 people in the world are infected with HIV. The majority of those infected live in developing countries
Keywords: HIV-infection; behavioral risks; awareness; lifestyle